Phase 2 Clinical Trial of Separation Surgery Followed by Stereotactic Body Radiation Therapy for Metastatic Epidural Spinal Cord Compression - Ito, Kei; Sugita, Shurei; Nakajima, Yujiro; Furuya, Tomohisa; Hiroaki, Ogawa; Hayakawa, Sara; Hozumi, Takahiro; Saito, Makoto; Karasawa, Katsuyuki (International journal of radiation oncology, biology, physics, 2022)
Stereotactic body radiation therapy (SBRT) is a postoperative treatment option for spinal metastases. Because data on surgery with SBRT are limited to retrospective studies, this single-center, single-arm, phase 2 study aimed to prospectively evaluate the outcomes of separation surgery and SBRT for metastatic epidural spinal cord compression (MESCC). Patients with symptomatic MESCC due to a solid carcinoma were enrolled. The protocol for treatments comprised preoperative embolization, separation surgery, and spine SBRT. Surgical procedures were performed via the posterior approach, with decompression and a fixation procedure. The prescribed dose for spine SBRT was 24 Gy in 2 fractions. The primary endpoint was the 12-month local failure rate. The secondary endpoints were ambulatory functions and adverse effects. A total of 33 patients were registered between November 2017 and October 2019. All patients met the inclusion criteria, and all but 1 completed the protocol treatment. Of the included patients, 23 (70%) had radioresistant lesions. The Bilsky grade at registration was 1c in 3 patients, 2 in 8 patients, and 3 in 21 patients. The median follow-up duration after registration was 15 months (range, 3-35 months). Three months after the administration of treatments according to the protocol, 90% of patients (26 of 29) had disease of Bilsky grade ≤1. The 12-month local failure rate was 13%. Twenty patients could walk normally or with a cane 12 months after registration. Radiation-induced myelopathy, radiculopathy, and vertebral compression fracture were observed in 0, 1, and 6 patients, respectively. Separation surgery with SBRT for MESCC was effective in decompression and long-term local control. These findings suggest that larger randomized controlled trials are warranted to compare SBRT with conventional radiation therapy.